Radiation exposure from diagnostic nuclear medicine in Alagoas (Brazil) in 2002-2005 - Yano, V. F.; Lima, F. F. (Cellular and Molecular Biology, 2010)
Use of radionuclides in medical practice has grown steadily in recent years due to the introduction of new radiopharmaceuticals and new equipments. This paper presents a survey of nuclear medicine procedures performed in Alagoas, State of Brazil, in order to help establish reference levels for nuclear medicine patients. Data were gathered on the type of radiopharmaceuticals used and administered activity of each kind of examination, and the age and sex of the patients involved over the period 2002-2005. Based on ICRP-60, the effective dose (E) and collective effective dose (Ecol) have been calculated. The results showed an annual increase in the nuclear medicine examinations during the period of study and cardiac scintigraphy are the most common procedure. The results also indicated that the activities administered to patients are higher than the guidance levels of the Basic Safety Standards (BSS) in most of the kind of examinations. The differences found in the administered activities may reflect the differences in the quality assurance programs implemented. It was observed that the Ecol and E/inhabitant are higher than other countries. Therefore, it is suggested that the protocols have been revised in order to reduce the patient dose without reduce the image quality.